Penguatan Brand Awareness Pada UMKM Bakso Raja Sapi - Edi Komara; Santi Rimadias; Siti Kolila; Nurul Luthfia (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Increasing brand awareness is an important strategy to foster strong customer relationships, drive business growth, and strengthen the company's position in the market. Continuous brand awareness is very important, especially for Micro, Small, and Medium Enterprises (MSMEs) who want to expand their market reach. Bakso Raja Sapi, an MSME in the food industry, has traditionally operated with a conventional business model, without focusing on marketing expansion. Through observations and interviews with business owners, it is clear that there is a need to increase their brand awareness. This community service activity is designed to address this gap by providing mentoring and practical insights on effective marketing tactics. This initiative aims to equip Bakso Raja Sapi with the necessary skills and knowledge to increase brand awareness. The results of this assistance include the development of visually appealing banner designs, the implementation of price bundling strategies, and the creation and management of social media presence. Community service activities show a substantial increase in the understanding and ability of owners to carry out marketing promotions to strengthen brand awareness. These efforts are expected to make Bakso Raja Sapi able to build a stronger brand identity and increase its competitiveness in the market.